2013
DOI: 10.1016/j.irfa.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and risk reporting in South Africa: A study of corporate risk disclosures in the pre- and post-2007/2008 global financial crisis periods

Abstract: The 2007/2008 global financial crisis has reignited the debate regarding the need for effective corporate governance (CG) through sound risk management and reporting practices. This paper, therefore, examines the crucial question of whether the quality of firm-level CG has any effect on the quality and extent of corporate risk disclosures (CRD) in South Africa (SA) with particular focus on the pre-and post-2007/2008 global financial crisis period. Using one of the largest datasets to-date on CG and CRD, from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

68
605
14
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 336 publications
(696 citation statements)
references
References 82 publications
(292 reference statements)
68
605
14
9
Order By: Relevance
“…Studies that investigated the nature of risk disclosure have reported that the disclosures are qualitative with a gap in disclosing forward-looking information (Beretta & Bozzolan, 2004;Dobler et al, 2011;Ntim et al, 2013).…”
Section: Review Of Previous Research and Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies that investigated the nature of risk disclosure have reported that the disclosures are qualitative with a gap in disclosing forward-looking information (Beretta & Bozzolan, 2004;Dobler et al, 2011;Ntim et al, 2013).…”
Section: Review Of Previous Research and Theoretical Backgroundmentioning
confidence: 99%
“…Many studies suggest that risk-related disclosure is used by companies to signal the quality and strength of their risk management processes, and their ability to identify, assess, and manage risk. An improved level of risk disclosure allows them to distinguish themselves from other companies with less effective risk management processes (Ntim et al, 2013;Abraham & Shrives, 2014).…”
Section: Review Of Previous Research and Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations